(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
In this work, the geometric meaning of the double integral and its behavior in sign-preserving and sign-changing functions are analyzed using rigorous mathematical methods. The difference between the concepts of “algebraic volume” and “true volume” is proven based on the properties of continuous functions and Riemann sums.